(untitled) (Quinto Sol, 2013)
This paper attempts to examine the raising of a network of institutions, comedores escolares [welfare kitchens] in the National Territory of la Pampa during the 1930’s, whose action was based upon the protection and defense of the most vulnerable infants. The analysis of this process shows the leading role of different state agents, the relationships that took place among different jurisdictions such as national, provincial and communal ones, as well as the role of community in the concrete implementation of public policies.